Students’ Ability in Identifying Referential Relation in Reading Text - Tini Mogea (Student Research Journal, 2023)
The purpose of this study is to describe students' ability to identify referential relationships in reading text.This research is quantitative research in percentage form. This research is conducted at SMP Negeri 1 Ratahan. The sample for this research is the third grade students of SMP Negeri 1 Ratahan, which consists of 32 students. The information is gathered using a multiple-choice objective-type test. The findings of this study indicate that the students involved in this study are very good at identifying referential relationships of personal type. This is very good in terms of the students' ability to identify referential relations of the personal pronoun type. Students perform poorly when it comes to identifying referential relations of the substitutional type. Students perform poorly when it comes to identifying elliptic type relations.